The Gastrodiplomacy Model as an Optimization of the Sustainable Tourism Sector in Semarang City - Kamal Ramadhani; Amir Mahmud; Moch Faizal Rachmadi (Politeknik Negeri Bali, 2026)
Gastrodiplomacy has increasingly been recognized as a strategic approach to promote cultural identity and tourism development through culinary heritage. However, most existing studies focus on gastrodiplomacy at the national level, whereas research on city-level gastrodiplomacy models integrated with sustainable tourism systems remains limited. This study aims to examine the role of gastrodiplomacy in optimizing the sustainable tourism sector in Semarang City, Indonesia. This research employs a qualitative descriptive approach involving 20 informants representing the ABCGM stakeholders (academics, business actors, communities, government, and media). Data were collected through in-depth interviews, observation, and documentation. The validity of the data was ensured through source and methodological triangulation, and the data were analyzed using the Miles and Huberman interactive analysis model, including data reduction, data display, and conclusion drawing. The findings reveal that Semarang's gastrodiplomacy is manifested through three main culinary clusters: milkfish, herbal medicine, and lumpia, which function as cultural and economic assets for tourism promotion. The study identifies that the effectiveness of gastrodiplomacy depends on stakeholder collaboration, the development of culinary identity, tourism integration, and digital promotion strategies. This study proposes an integrated gastrodiplomacy model that connects culinary clusters, tourism destinations, transportation accessibility, and multi-stakeholder collaboration to strengthen sustainable tourism development. The findings contribute theoretically by expanding the gastrodiplomacy literature from a city-level sustainable tourism perspective, while offering practical policy insights for developing culinary-based destination branding and strengthening local economic resilience.